P-013 Pre-diagnostic Antibodies Against Salmonella Typhi Are Associated with Development of Crohn's Disease, Potentially Modified by Crohn's Disease Predisposing Risk Variants. (March 2016) - Brant, Steven; Cihakova, Daniela; Al Kazzi, Elie; Vladut-Talor, Monica; Wu, Yuqiong; Ramos, Miquel Alfonso; Huang, Chengrui; Hall, Noah; Jaqua, Nathan; Datta, Lisa; Singla, Manish; Hutfless, Susan
Abstract : Background: Numerous genetic risk factors predispose individuals for Crohn's disease (CD). Monozygotic twin concordance is only ∼30%, suggesting that environmental factors are required to "trigger" CD development in predisposed individuals. Previously, Salmonella positive stool cultures have been found increased in years prior to CD diagnosis, although the association has been attributed to detection bias. We evaluated anti-Salmonella typhi IgG antibodies from sera collected at multiple time points for cases and matched controls as an unbiased evaluation of Salmonella exposure on CD risk. We also evaluated whether established CD predisposing variations in NOD2, ATG16L1, IRGM, CARD9 or FUT2 innate-immunity genes interact with Salmonella infection to alter CD risk. Methods: Sera and blood were obtained from active duty U.S. military personnel that had >2 CD ICD-9-CM diagnostic codes and from unaffected controls matched by service branch, enlistment status, race, sex and age with samples from the same time periods. Information was collected with regard to the case's diagnosis date labeled as the index date. Anti-Salmonella typhi IgG antibodies were determined by ELISA using a commercial assay on 3 sera samples from each subject: one obtained >3 years prior to the index date (pre-2), between 3 years and 3 months prior (pre-1) to the index date, and between 3 months prior to 24 months after the index date. DNA was purified from blood and genotyped for presence of NOD2, ATG16L1, IRGM, CARD9 or FUT2 CD risk variations. Anti-Salmonella antibodies were evaluated at each time period for association with CD diagnosis and for interaction with CD predisposing variations accounting for matching factors and military deployment, which often results in vaccination for Salmonella typhi. Results: Nine hundred eighty-two CD cases and 998 matched controls were evaluated. Anti-Salmonella typhi IgG antibodies in one or more sera samples was greater in cases than controls (14% versus 8%, P < 0.0001). Cases were more likely to have detectable antibodies at each time point (pre-2 OR 1.9, 95% CI 1.2–3.0, P = 0.003; pre-1 OR 1.6, 95% CI 1.1–2.4 P = 0.01; index OR 2.3, 95% CI 1.5–3.4, P < 0.0001). Deployments were inversely associated with later CD diagnosis. CD predisposing variations were more frequent in cases for each gene with the exception of CARD9, and reached statistical significance ( P < 0.05) for NOD2, IRGM and FUT2. No risk genotypes showed significant interactions with anti-Salmonella antibodies associated with future CD risk, although the FUT2 secretor variation showed borderline significance for the pre-1 period ( P = 0.06), and NOD2 mutations and ATG16L1 wildtype variations showed trends of interest in the pre-2 period, ( P = 0.16 and 0.17, respectively). Conclusions: Military personnel diagnosed with CD have approximately 2-fold greater frequency of IgG antibodies to Salmonella typhi, even 3 or more years prior to CD diagnosis This finding promotes the concept that pathogens that cause acute intestinal inflammation may predispose individuals to later development of CD, perhaps by causing initial intestinal inflammation or microbiomic alterations. An effort to identify individuals with CD predisposing genetic variations to target Salmonella preventive strategies was not successful, although variations in FUT2, NOD2 and ATG16L1 showed findings deserving of further evaluation.